Corporate Social Responsibility Practices of Global Automakers in Asia: Application of Carroll Model with Multi-Case Study Method - Mr. Siddhartha Tomar, Dr. Pooja Sangwan, Dr. Mannat Singh, Dr. Rekha Dahiya (Journal of Informatics Education and Research, 2024)
In spite of acknowledging the importance of sustainable and socially responsible practices; researchers have not been able to unanimously identify the priority areas of CSR for the automotive sector. This research was designed to understand the CSR activities of the global automakers in the Asian countries by applying the Carroll model wherein researchers wished to analyse the CSR programs of the global automakers, identify the priority CSR areas and assess the effect of CSR strategies on business performance of global automakers. Case study method was used in the existing study. This study utilised multiple case study research strategy whereby two automobile companies were studied in depth namely, Toyota and Volkswagen. The data for the study was secured from different- structured data sources like company reports, sustainability data records and media coverage. Data was analysed using content analysis. The study concluded that both companies are widely engaged in CSR initiatives that covered ethical, philanthropic, legal, and economic responsibilities. Toyota focused on their production process and policies that was employee centric, Volkswagen worked on industry modernization as well in their ethical practices. The philanthropic initiatives at both places worked towards education/training, employment generation, collaborations/partnerships, environmental and social welfare. Volkswagen also focused on sports and, art and cultural aspects in their humanitarian responsibilities. Both the peers were on the same page regarding economic practices where the cutting costs and improving efficiency was in focus. Both Toyota and Volkswagen gave more priority to the philanthropic and ethical aspect than the economic aspect. Both the companies experienced similar outcomes from these CSR initiatives like positive financial measures, quality metrics, brand identity improvement and differentiation, worker and consumer satisfaction, risk management and aversion, improved partnership opportunities.